Investigating Positive Perceptions of High School Students' Distance Learning Experiences During a Pandemic - Agus Purnomo Ahmad Putikadyanto; Gamal Kusuma Zamahsari; Wiga Alif Violando (Abjadia, 2021)
COVID-19 has driven pedagogical transformation in the most unexpected and sudden way in education history. Students must switch from face-to-face to distance learning. Trough quantitative research model, this study aims to describe high school students' perceptions of distance learning. Samples were collected from school which might prepare their students for distance learning. Using a questionnaire data collection technique, a sample of 70 high school students received 40 questions derived from three perceptual indicators, namely absorption, understanding, and assessment. The results of this study's absorption, understanding, and assessment indicator scores which were higher than the median indicated that students' perceptions of distance learning were typically positive. This occurs as a result of collaboration between students, teachers, and school staff to accomplish effective distance learning.